2022
DOI: 10.1002/mp.15481
|View full text |Cite
|
Sign up to set email alerts
|

Intraradiological pathology‐calibrated electrical impedance spectroscopy in the evaluation of excision‐required breast lesions

Abstract: Evaluating a real-time complementary bioelectrical diagnostic device based on electrical impedance spectroscopy (EIS) for improving breast imagingreporting and data system (BI-RADS) scoring accuracy, especially in high-risk or borderline breast diseases. The primary purpose is to characterize breast tumors based on their dielectric properties. Early detection of high-risk lesions and increasing the accuracy of tumor sampling and pathological diagnosis are secondary objectives of the study. Methods: The tumor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The TN-IMS response was calculated by analyzing the dielectric properties of thyroid samples obtained via two impedimetric classification parameters of Z 1kHz and IPS. These two parameters have been used in previous studies on cancerous breast tumor margins and involved lymph nodes with promising results [ 28 , 29 ]. According to the surgeon’s diagnosis, these two parameters were recorded for each palpable thyroid nodule or any area that seemed suspicious.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TN-IMS response was calculated by analyzing the dielectric properties of thyroid samples obtained via two impedimetric classification parameters of Z 1kHz and IPS. These two parameters have been used in previous studies on cancerous breast tumor margins and involved lymph nodes with promising results [ 28 , 29 ]. According to the surgeon’s diagnosis, these two parameters were recorded for each palpable thyroid nodule or any area that seemed suspicious.…”
Section: Resultsmentioning
confidence: 99%
“…The TN-IMS tested at least three points of each nodule with a measurement time of 3 s to cover all the nodule areas because of the heterogeneous nature of high-risk thyroid nodules [ 28 ]. The ECG lead was connected to the submental region at the beginning of surgery during preparation of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the use of CNB is recommended for the FNAC interpretation. [15] After core biopsy, all 37 cases of BIRADS 5 lesions that were declared malignant on radiography were found to be malignant. As a result, the BIRADS 5 lesions had a 100% positive predictive value for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Impedimetric detection is performed using a handheld intraoperative ITDS, which extracts two classification parameters: Z1kHz (impedance magnitude at f = 1 kHz) and IPS (Impedance phase slope in the frequency range of 100 kHz–500 kHz) (Figure 3). These two parameters were previously introduced and evaluated in several projects to diagnose breast tumor margins, intraradiological breast tumor detection, and the diagnosis of involved lymph nodes in breast cancer patients 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Many previously released reports reveal that EIS can alter clinical management and improve accuracy. [12][13][14] In this regard, Svoboda et al assessed the impact of EIS results on clinicians' diagnostic accuracy and biopsy decisions. The results showed that the EIS score could lead to a change in the decision to biopsy in 25% of cases, improving diagnostic accuracy and resulting in fewer biopsies of benign lesions and more biopsies of melanomas.…”
Section: Eis In Clinical Practicementioning
confidence: 99%